Synthesis and Characterisation of Bentonite/Poly(Acrylic Acid) Hybrid Material for Its Application as A Catalyst in Esterification of Glycerol with Acetic Acid - Sholehah, Hidayati Nur Mohammad; Suwardiyanto; Tanti Haryati; Novita Andarini; Sulistiyo, Yudi Aris (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
Bentonite/poly(acrylic acid) (BTAA) hybrid material commonly applied as superabsorbent was prepared via intercalation method coupled with in situ polymerisation of partially neutralised acrylic acid monomers. The structural characteristics of various BTAA ratios and their constituents were scrutinised using XRF, XRD, and FTIR. Basal spacing of BTAA hybrid materials decreased as a result of intercalation with polyacrylic acid. Interaction between bentonite and polyacrylic acid was also observed in the shifting and reduced intensity of O–H, C=O, and Si–O–Al absorption bands. Catalytic activity of BTAA was investigated through its ability to facilitate the esterification reaction of glycerol with acetic acid. The result suggests that catalytic activity is present in BTAA hybrid materials, as evidenced by the production of monoacetin and triacetin.